Measuring The Proportion Of Time Spent On Work Activities Of Clinical Pharmacists At A Public Hospital And The Public Perception And Satisfaction Towards Hospital Pharmacists’ Services In Malaysia - Kong, Kian Keong (2023)
The role and work activities of hospital pharmacists have recently changed under the impact of the public services revamp in Malaysia, with a scarcity of updated evidence available today. Furthermore, the evidence on the public’s perception of hospital pharmacists was still lacking in Malaysia. This study aimed to identify the role and work activities of public hospital-based clinical pharmacists from the observer's and the general public perspective. The study was conducted in two phases. In the first phase, a work sampling study was conducted by making 1455 random observations using two observers over 30 days on the work activity of 5 clinical pharmacists working in the public hospital. A total of 3493 events were recorded. Overall, clinical pharmacists spent 78.8% (n=2751) of their time providing clinical services whereas 12.3% (n=433) of their time was spent on non-clinical activities. They were found to be idle from work for 8.9% of the time. Clinical pharmacists were found to report a higher average daily cumulative work unit of 9.8 (SD = 4.3) when under observation compared to an average daily cumulative work unit of 6.5 (SD = 4.6) when no observer was present (p=0.005). In general, a significant amount of time of the clinical pharmacist in the public hospital was spent on non-clinical work. Many efforts spent by the clinical pharmacists were not captured by the work reporting information system.